Analisis beban kerja terhadap kebutuhan sumber daya manusia pada unit rekam medis di puskesmas - Herisma Putri Fandarina; Helmi Nurlaili (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: Community Health Center is a health service facility that organizes public health efforts. Pejagoan Health Center is one of the Health Units in the Kebumen Regency area, which coincides in Pejagoan District and houses 13 villages that carry out various health service activities, one of which is medical record services. Medical Record is the activity of recording patient documents. They have 3 medical record officers with various educational backgrounds and visitor data. In 2020, 28,652 total visitors were found.Objective: The studywas aimed to find out the need for human resources at the UPTD Medical Record Unit at Pejagoan Health Center Kebumen.Methods: The study uses quantitative descriptive and uses secondary reports from related parties as well as a calculator instrument to trade time variables, besides that this study refers to the WISN.Results: There are only 3 medical record officers at the puskesmas with 1 person having medical record education. From the results of the calculation, the Pejagoan Health Center Medical Record Unit requires 6 human resources to meet the workload standards following the job descriptions.Conclusion: Pejagoan Health Center Medical Record Unit requires 6 human resources to meet the workload standards following the job descriptions.